(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
The article discusses the issues of automation of grain storage in silos and elevators, the use of this system will make it "transparent", ensure the stability of the process and the profitability of the agricultural enterprise, plan resources and budget, organize the coordinated work of structural and functional divisions, create a single information field for contractors and customers. The article analyzes the automation system taking into account the control of technological parameters, including temperature, humidity using modern measuring instruments. Options for controlling humidity and temperature parameters with the use of various structural automation schemes are discussed, appropriate recommendations are given for the further use of automation tools for full automation of the grain storage process.